Stage at diagnosis and colorectal cancer survival in six high-income countries: A population-based study of patients diagnosed during 2000–2007. (June 2013) - Maringe, Camille; Walters, Sarah; Rachet, Bernard; Butler, John; Fields, Tony; Finan, Paul; Maxwell, Roy; Nedrebø, Bjørn; Påhlman, Lars; Sjövall, Annika; Spigelman, Allan; Engholm, Gerda; et al.
Abstract Background. Large international differences in colorectal cancer survival exist, even between countries with similar healthcare. We investigate the extent to which stage at diagnosis explains these differences. Methods. Data from population-based cancer registries in Australia, Canada, Denmark, Norway, Sweden and the UK were analysed for 313 852 patients diagnosed with colon or rectal cancer during 2000–2007. We compared the distributions of stage at diagnosis. We estimated both stage-specific net survival and the excess hazard of death up to three years after diagnosis, using flexible parametric models on the log-cumulative excess hazard scale. Results. International differences in colon and rectal cancer stage distributions were wide: Denmark showed a distribution skewed towards later-stage disease, while Australia, Norway and the UK showed high proportions of 'regional' disease. One-year colon cancer survival was 67% in the UK and ranged between 71% (Denmark) and 80% (Australia and Sweden) elsewhere. For rectal cancer, one-year survival was also low in the UK (75%), compared to 79% in Denmark and 82–84% elsewhere. International survival differences were also evident for each stage of disease, with the UK showing consistently lowest survival at one and three years. Conclusion. Differences in stage at diagnosis partly explain international differences in colorectal cancer survival, with a more adverse stage distribution contributing to comparatively low survival in Denmark. Differences in stage distribution could arise because of differences in diagnostic delay and awareness of symptoms, or in the thoroughness of staging procedures. Nevertheless, survival differences also exist for each stage of disease, suggesting unequal access to optimal treatment, particularly in the UK.